Urgensi Pembentukan Karakter Cinta Tanah Air melalui Pendidikan Pancasila - Suroto, Fitri Indriani; Najicha, Fatma Ulfatun (Program Studi PPKn, Fakultas Keguruan dan Ilmu Pendidikan Universitas Buana Perjuangan Karawang, 2023)
The attitude of love for the motherland is one of the contents of the noble values ​​of Pancasila which became the basis for the establishment of the independent nation and state of Indonesia. One of the positive values ​​that need to be instilled in students through the learning process as the next generation of the nation is the character of loving the motherland. Seeing the current reality, many young people are starting to lose their love for their homeland along with the era of globalization and modernization. This study aims to examine the role of Pancasila education in the formation of the character of loving the homeland by using a qualitative descriptive method. The importance of Pancasila education in creating young people as pillars of the nation has a very important role. Pancasila character education is not only limited to answering actual problems and being used as an educational advertising commodity, but there are future achievements that must be achieved, namely building a sovereign, independent and superior nation based on a sense of love for the motherland as a strong roots in implementation.